PENGARUH KEPUASAN KERJA TERHADAP DISIPLIN KERJA KARYAWAN CV. KAMPAR MOTOR KABUPATEN KAMPAR - Lamin, Lamin (Sekolah Tinggi Ilmu Ekonomi Riau, 2018)
The title of this study is the effect of job satisfaction on the discipline of honorary employee CV Kampar Motor. Populasi in this study is all employees honorer who amounted to 38 employees sampled research. Results of SPSS Examination in this study found the test results on Job Satisfaction variable (X) on Work Discipline (Y) can be seen that t-count is greater than t-table (7,929> 2.028) with significant level 0,00. It can be concluded that job satisfaction variable (X) has a positive and significant effect on employee work discipline (Y) The result of simple linear regression shows Y = a + bX namely: Y = 7.026 + 0.870X. From the regression equation it is concluded that the regression coefficient of bx is positive. This indicates that the independent variable if the enhanced equation will give rise also to the dependent variable. R Square results of 0.636 (63.6%) explained that the discipline of of the respondent is influenced by job satisfaction of 63.6%